(untitled) (Research, Society and Development, 2021)
The means of dissemination of scientific production in Brazil, better known as scientific journals, have the qualis journal system, of the Coordination for the Improvement of Higher Education Personnel (Capes), as one of their main classification systems, and as a result of the dynamics of the production and dissemination of scientific knowledge, currently, there is no system that does not require periodic adjustments. Thus, this qualitative research, through a literature review, aims to discuss some aspects of the process of dissemination of scientific knowledge and, mainly, the new Capes methodology proposal for journal classification that will be in force from this year, 2021, when it is publication of the final version of the new Qualis Periodicals, also called Qualis Capes or Qualis Periodicals Reference. For a better visualization of the comparison between the old and the new format, a table with the number of journals in both, in each stratification category, and a graph representing this quantitative difference by stratification were created. In this way, it was noticed that, despite the initial discomfort from any proposal or change process, it is necessary and the creation of a single large area, in the context in question, it will facilitate the assessment made by Capes.